Changing trend of antimicrobial susceptibility pattern of Salmonella species isolated at Kathmandu Medical College Teaching Hospital. - Pradhan, SB; Shrestha, CD (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: The present study was designed to analyze the antibiotic susceptibility pattern of Salmonella species and to determine the changing trend of antimicrobial susceptibility pattern of Salmonella speciesMethod: A total of 100 isolates of Salmonella species among all the blood culture samples in KMCTH lab from March 5th 2011 onward were taken into a study group and antibiotic sensitivity test was performed by Kirby Bauer’s method.Result: Out of 100 positive samples, 93 were found to be Salmonella typhi and 7 were Salmonella paratyphi. Salmonella typhi was found to be 100% sensitive to Ciprofloxacin, Amikacin & Erythromycin. Nalidixic acid was found to be the least sensitive (86.02%). Other frequent resistant antimicrobial were Ceftriaxone (7.52%), Cotrimoxazole (4.3%), Chloramphenicol (3.22%) and Ampicillin (1.07%). Similarly, Salmonella paratyphi was found to be 100% sensitive to Ciprofloxacin & Amikacin. In addition to this Chloramphenicol, Erythromycin and Nalidixic acid were also 100% sensitive but were resistant to Ceftriaxone (28.57%), Ampicillin (28.57%) and Cotrimoxazole (14.28%).Conclusion: The emergence of Salmonella typhi and paratyphi resistant to Ceftriaxone is of very great concern.